PERFORMANCE COMPARISON ANALYSIS OF SPRINGBOOT AND LARAVEL FRAMEWORKS USING API WEB SERVICE - Rizky Yulianto; Mardiana Mardiana; Rio Ariestia Pradipta; Gigih Forda Nama (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
This study is meant to know difference in performance between web service built with Laravel and Spring Boot. To know the performance of both framework two web service is made with Representational State Transfer Application Interface or (REST API) as a common means to communicate to send data with Create, Read, Update, and Delete (CRUD) method to a similar database. The response time Performance from both of the framework is calculated by simulating usage that is 10000 request for each method Post, Get, Update, and Delete. The result from the test of Spring Boot and Laravel using Apache Jmeter is that with 10000 request using Postt, Get, Put and Delete method in order Spring Boot has request time advantage that is 44,8ms, 45,37ms, 109,5ms, 42ms compared Laravel 291,98ms, 301,2ms, 426,54ms, 273,06ms.